Application of hand scraping therapy combined with Baduanjin exercise to relieve peripheral neurotoxicity and anxiety induced by oxaliplatin-based chemotherapy: A case report (手部刮痧疗法联合八段锦改善奥沙利铂化疗所致外周神经毒性合并焦虑情绪1例的护理体会) - SUN Yanan (孙亚南); WANG Yuhui (王玉慧); CHEN Yang (陈扬) (Association of Integrative Nursing, 2023)
This paper reviewed the hand scraping therapy combined with Baduanjin exercise for a patient with peripheral neurotoxicity and anxiety induced by oxaliplatin-based chemotherapy. The technique of hand scraping therapy, acupoint selection and method of Baduanjin exercise were summarized. Based on basic theory of Traditional Chinese Medicine syndrome differentiation, appropriate nursing techniques were carried out to relieve the numbness in both hands and negative emotion of patient, and ensure successful completion of chemotherapy. (本文总结1例晚期恶性肿瘤患者因奥沙利铂化疗所致外周神经毒性合并焦虑情绪采用手部刮痧疗法联合八段锦治疗的效果和护理体会, 包括刮痧的手法、穴位以及八段锦的锻炼等。基于中医基础理论, 辨证采取中医护理适宜技术, 能有效改善患者双手麻木症状, 缓解负性情绪, 有利于患者顺利完成周期化疗。)